EFFECT OF Al, Zr AND Mo ON CORROSION RESISTANCE OF AlXCrFeNiMo AND AlXCrFeNiZr (X=1, 1.2 AND 1.4) AS FUEL CLADDING MATERIALS - Teguh Firmansyah; Bonita Dilasari; Jan Setiawan; Djoko Hadi Prajitno (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2022)
EFFECT OF Al, Zr AND Mo ON CORROSION RESISTANCE OF AlXCrFeNiMo AND AlXCrFeNiZr (X=1, 1.2 AND 1.4) AS FUEL CLADDING MATERIALS. The high entropy alloy of AlxCrFeNiM (with x = 1, 1,2 and 1,4; M = Mo and Zr) was successfully synthesized using powder metallurgy technique with sintering process at 1000 oC in an inert atmosphere. These alloys were designated as fuel cladding for research reactor with high U-density fuel such as U-Mo. One of the critical in-service properties of nuclear fuel cladding is its corrosion behavior. In this study, some properties of the HEA of AlxCrFeNiM such as the phases, microstructures, hardness, and corrosion resistance in 3 wt.% NaCl solution at room temperature were investigated. The results show that the phases in the HEA of AlxCrFeNiMo are FeNi, AlNi and Mo. The HEA of AlxCrFeNiZr has more complex phases compared to the AlxCrFeNiMo. The microstructure of HEA samples show  fine grains with some micropores that imperfect the solidification during the sintering process. The hardness value of the HEA of AlxCrFeNiMo has a trend of decreasing as the x value increases. The opposite trend occurs to the HEA of AlxCrFeNiZr that the hardness value increases with increasing x value. The lowest hardness value is Al1.4CrFeNiMo at 262.2 HV, and the highest hardness value of Al1.4CrFeNiZr is at 756.7 HV. The corrosion rate of the AlxCrFeNiMo does not show a specific trend with increasing x value; however,  the AlxCrFeNiZr shows decreasing value with increasing x value. The lowest value for the all-HEA samples is 0.20 mmpy for the Al1.4CrFeNiZr. The results of hardness and corrosion tests show that the Zr element combined with the Al element affects not only its hardness but also its corrosion resistance.Keywords: Fuel cladding, high entropy alloy, corrosion